Pbp1-Interacting Protein Mkt1 Regulates Virulence and Sexual Reproduction in Cryptococcus neoformans - Son, Ye-Eun; Fu, Ci; Jung, Won-Hee; Oh, Sang-Hun; Kwak, Jin-Hwan; Cardenas, Maria E.; Heitman, Joseph; Park, Hee-Soo (Frontiers in Cellular and Infection Microbiology, 2019)
The Mkt1–Pbp1 complex promotes mating-type switching by regulating the translation of HO mRNA in Saccharomyces cerevisiae. Here, we performed in vivo immunoprecipitation assays and mass spectrometry analyses in the human fungal pathogen Cryptococcus neoformans to show that Pbp1, a poly(A)-binding protein-binding protein, interacts with Mkt1 containing a PIN like-domain. Association of Pbp1 with Mkt1 was confirmed by co-immunoprecipitation assays. Results of spot dilution growth assays showed that unlike pbp1 deletion mutant strains, mkt1 deletion mutant strains were not resistant to heat stress compared with wild-type. However, similar to the pbp1 deletion mutant strains, the mkt1 deletion mutants exhibited both, defective dikaryotic hyphal production and reduced pheromone gene (MFα1) expression during mating. In addition, deletion of mkt1 caused attenuated virulence in a murine intranasal inhalation model. Taken together, our findings reveal that Mkt1 plays a crucial role in sexual reproduction and virulence in C. neoformans.